1990
DOI: 10.1017/s0308229600018626
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia and its attempted control in newborn piglets

Abstract: The newborn piglet is prone to hypothermia because of the body heat which is lost in evaporating birth fluids from its surface and because the climatic environment provided for the piglet at birth can be sub-optimal. If deep body temperature drops by over 2°C from the norm of 39° C the pig suffers from reduced locomotor vigour and becomes, more lethargic (Stephens, 1971). Such disadvantages can make the piglet less effective in competing for a teat and colostrum and also more prone to be overlain by the dam (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 0 publications
3
14
1
Order By: Relevance
“… Caldara et al (2014) found that the minimum body surface temperature was reached at 15 min after birth. However, similar to the current experiment, a number of studies have found that the minimum temperature occurred at 30 min after birth ( Pattison et al, 1990 ; Andersen and Pedersen, 2015 ; Xiong et al, 2018 ; Cooper et al, 2019 ). There was considerable variation in the estimates of minimum temperatures between these studies, ranging from 33.6 °C ( Xiong et al, 2018 ) to 36.6 °C ( Pattison et al, 1990 ).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“… Caldara et al (2014) found that the minimum body surface temperature was reached at 15 min after birth. However, similar to the current experiment, a number of studies have found that the minimum temperature occurred at 30 min after birth ( Pattison et al, 1990 ; Andersen and Pedersen, 2015 ; Xiong et al, 2018 ; Cooper et al, 2019 ). There was considerable variation in the estimates of minimum temperatures between these studies, ranging from 33.6 °C ( Xiong et al, 2018 ) to 36.6 °C ( Pattison et al, 1990 ).…”
Section: Resultssupporting
confidence: 84%
“…In addition, Kammersgaard et al (2011) reported considerable variation in birth temperatures within the same study (37.0 to 41.5 °C). Given that piglet temperature declines rapidly immediately after birth ( Pattison et al, 1990 ), differences between studies may be mainly due to the timing of measurement relative to the time of birth.…”
Section: Resultsmentioning
confidence: 99%
“… Pedersen et al (2016) found that confining piglets under a radiant heat source (at 34 °C) for 2 h compared to leaving them at room temperature (at 20.9 °C) increased the minimum temperature by between 1.2 and 1.4 °C, which is similar to the results for the Warming treatment in the current study. In contrast, Pattison et al (1990) showed a small increase in temperature (0.3 °C at 60 min after birth) from confining piglets in a heated creep area for 45 min. However, the warming treatment in that study started at 15 min after birth, by which time piglet temperatures would have decreased considerably.…”
Section: Resultsmentioning
confidence: 85%
“…At all other times, there were no differences (P > 0.05) between temperatures of medium and heavy piglets for any of the four treatments. Previous research has also shown that the extent and duration of the temperature decline after birth is greater in low birth weight piglets than in heavier littermates ( Pattison et al, 1990 ; Pedersen et al, 2016 ; Cooper et al, 2019 ; Vande Pol et al, 2020 ). Lighter piglets are predisposed to chilling ( Muns et al, 2016 ), having a high body surface area to volume ratio, low body fat for insulation ( Curtis, 1974 ), and limited energy reserves (glycogen and fat) for heat production ( Lossec et al, 1998 ).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation